Analisis Tingkat Kualitas Pelayanan Perizinan Menggunakan Metode Fuzzy Servqual - M. Almepal Wanda; Gunadi Widi Nurcahyo (Jurnal KomtekInfo, 2021)
The low quality of service is a problem that affects people's satisfaction. The Padang City One Stop Integrated Service and Investment Service, and sometimes it is problematic in assessing the quality of its services. The object of the study is to see the Service quality of Community Licensing in the Padang City DPMPTSP. In this research, there are 15 respondent data originating from the licensing and complaints section of the Padang City DPMPTSP. Based on the analysis of the data, a research was conducted on the quality of community satisfaction. The fuzzy servqual method can be used to explain the uncertainty about information about certain parts of the problem at hand, such as community satisfaction, response quality, expectations and service quality. The results of this research show the distribution data and the percentage of business actor satisfaction quality on service performance so that it can be seen that 47.41% of business actors are satisfied with the performance of the service and 52.59% of business actors who assess the Padang City DPMPTSP service as very satisfactory. Conclusion From the test results Fuzzy servqual method has been able to provide knowledge on the quality of service quality. To assist the licensing and complaints department in improving the service quality of the Padang City DPMPTSP.